Research on 3D Development Characteristics of Water-Conducting Fractured Zone Based on Field Measurement - Feng, Dong; Hou, Enke; Wang, Shuangming; Xie, Xiaoshen; Yuan, Feng; Guo, Liangliang; Wang, Gang; Xie, Yongli; Chen, Zhen (Frontiers in Earth Science, 2022)
With the large-scale mining of coal resources in western China, coal resources are gradually shifting from shallow to deep mining. Coal seam mining, the overlying rock water conducting fractured zone (WCFZ) is the main factor causing mine water damage and water resources damage. Accurately grasping the development height of the water-conducting fissure zone is the key to the prevention of water hazards and the protection of water resources in medium-deep coal seams. In this paper, the 3D development form of WCFZ in the middle and deep coal seam mining is studied by the integrated method of drilling and 3D seismic survey, taking the first mining face of Xiaobodang No.1 mine in Yushen mining area.The results of the study show that the height of WCFZ measured by drilling is 81.50 m ~ 177.07 m.The height of WCFZ development in the 3D seismic survey is 79.83 m ~ 178.03 m,and the morphology of WCFZ is saddle-shaped. This study provides methodological guidance for predicting the 3D morphology and developmental characteristics of wcfz. The results obtained are of great significance for the safe, green and efficient mining of coal seams in medium and deep buried ecologically fragile environments.